The Nature of Multiple Responses to Teachers' Questions. (10th April 2013) - Ko, Sungbae
Abstract : To contribute to a range of issues surrounding the dynamic and interactive nature of language classroom talk-in-interaction, this study examines dynamic origins and functions of multiple responses to teachers initiations, which can be considered as an intrinsic type of pedagogical interaction in ESL and EFL classroom talk, and probes how such classroom interaction provides an opportunity for learners to share participation and collaboratively achieve a local learning objective. To interpret and analyse the multiple response appropriately, this study uses tools of conversation analysis.